Immunocompromised rabbit model of chronic HEV reveals liver fibrosis and distinct efficacy of different vaccination strategies. Issue 3 (30th March 2022) - He, Qiyu; Zhang, Fan; Shu, Jingyi; Li, Shuangshuang; Liang, Zhaochao; Du, Minghao; Liu, Xing; Liu, Tianxu; Li, Manyu; Yin, Xin; Pan, Qiuwei; Lu, Fengmin; et al.
Abstract: Background and Aims: HEV infection can lead to chronicity and rapid progression to liver fibrosis and cirrhosis in immunocompromised organ transplant recipients. Robust animal models are urgently needed to study the pathogenesis and test the efficacy of vaccines and antiviral drugs in immunosuppressed settings. Approach and Results: Cyclosporin A was used to induce immunosuppression. Rabbits were challenged with genotype 3 or 4 HEV (i.e., the rabbit‐derived HEV3 and human‐derived HEV3 or HEV4). We assessed HEV markers within 13 weeks post inoculation (wpi) and pathological changes by hematoxylin and eosin and Masson staining at 4, 8, or 13 wpi. Chronic HEV infection was successfully established in immunocompromised rabbits. HEV RNA and/or antigens were detected in the liver, kidney, intestine, urine, and cerebrospinal fluid samples. Chronically infected animals exhibited typical characteristics of liver fibrosis development. Intrahepatic transcriptomic analysis indicated activation of both innate and adaptive immunity. Establishment of HEV chronicity likely contributed to the inhibited T‐cell immune response. Ribavirin is effective in clearing HEV infection in immunocompromised rabbits. Most interestingly, vaccination completed before immunosuppression conferred full protection against both HEV3 and HEV4 infections, but vaccination during immunosuppression was only partially protective, and the efficacy did not improve with increased or additional vaccine doses. Conclusions: The immunocompromised rabbit model of both chronic HEV3 and HEV4 infection that was established captured the key features of chronic HEV infection in transplant patients, including liver fibrogenesis, and revealed the distinct effectiveness of vaccination administered before or under immunosuppression. This rabbit model is valuable for understanding the pathogenesis of chronic hepatitis E, as well as for evaluating antiviral agents and vaccines. Abstract :